Impact of Excise to Retail Price of Cigarettes Case Study of Excise System Comparison in Indonesia for the Period of2005-2010 - Surjono, Nasruddin Djoko (Jurnal Kajian Ekonomi dan Keuangan, 2013)
This paper analyzes the impact of implementation of ad valorem , hybrid and specific excise system periods to tobacco price. The main hypothesis HO i.e. there is no difference impact of implementation of ad valorem , hybrid and specific system period to the price. The research question is to answer what fraction of excise is passed on to consumers in each excise systems period and which one of excise system periods has the greatest negative impact on price, which is important to know, when country makes choice on appropriate excise system policy in order to reform their excise system for tobacco control. Monthly data production from 2005-2010 is explored in order to estimate tax incidence in Indonesia. In this period Indonesia has implemented ad valorem , hybrid and specific excise system consecutively. With brands consumption data in Indonesia, the model analyzes by including burden of excise in each excise system in the model. The estimation result of tax incidence model indicates that during government implement specific excise system, the impact of increasing excise is relative higher to the price.